2020
DOI: 10.1002/hed.26534
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint expression in HNSCC patients before and after definitive chemoradiotherapy

Abstract: Background Primary platinum‐based chemoradiotherapy (CRT) remains the treatment of choice for nonresectable squamous cell carcinoma of the head and neck (HNSCC). Immune‐checkpoint modulators are used as palliative therapy and studied in combination with definitive CRT. However, the immunological changes by CRT need yet to be understood. Methods A cohort consisting of 67 paired tissue biopsies (N = 134) of HNSCC patients before and after CRT was created. The expression of PD‐1, PD‐L1, and CD27 of tumor and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Assessment of the PD-L1 status revealed that all patients with recurrences had a negative CPS. This finding is in accordance with our previously published paper, where we could show that PD-L1 expression is a protection against the occurrence of recurrences [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Assessment of the PD-L1 status revealed that all patients with recurrences had a negative CPS. This finding is in accordance with our previously published paper, where we could show that PD-L1 expression is a protection against the occurrence of recurrences [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…CD3E is expressed specifically on T cells and high expression could be linked to a favorable prognosis (35). In an earlier study on a slightly different cohort, we were already able to show a loss of expression of CD27, which is expressed on T cells and is a co-stimulatory molecule, on protein level (36). This supports the observation made here of a downregulation of these two genes in poor responder under therapy.…”
Section: Discussionsupporting
confidence: 87%
“…Since the classical approaches for identifying prognostic indicators in HNSCC, such as CT and MRI, no longer satisfy the clinical requirements for precision medicine ( 14 ), identification of novel prognostic markers and stratification of patients based on prognosis are warranted to provide new indicators for individualized precision treatment ( 15 ). On this premise, this study established CD27 expression as a potentially significant prognostic indicator in patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%